E-Policing dan Implikasi Kebijakan Pengelolaan Keamanan Publik - Lalu Guruh Prawira Negara (Jurnal Syntax Admiration, 2024)
This study aims to analyze the implementation of E-Policing in the management of street crime reports in Depok City in the period May to August 2024. By utilizing information and communication technology, E-Policing functions to increase efficiency, speed, and accuracy in crime reporting and handling. The method used in this study is a combination of quantitative surveys and qualitative interviews from the people of Depok City. The results of the study show that the implementation of the "Halo Police" Application has improved the ease of crime reporting, accelerated police response, and strengthened community involvement in security surveillance. The public feels more satisfied with police services after the implementation of E-Policing through the "Halo Police" Application. However, for now the use of the "Halo Police" Application is still uneven and only exists in urban communities, it is a challenge for the government to be able to increase the equitable distribution of the system to make it easier for the community, which contributes to increasing public involvement in maintaining security.